Xanthone-1,2,4-triazine and Acridone-1,2,4-triazine Conjugates: Synthesis and Anticancer Activity - Sougata Santra; Ainur D. Sharapov; Ramil F. Fatykhov; Anastasya P. Potapova; Igor A. Khalymbadzha; Maria I. Valieva; Dmitry S. Kopchuk; Grigory V. Zyryanov; Alexander S. Bunev; Vsevolod V. Melekhin; Vasiliy S. Gaviko; Andrey A. Zonov (MDPI AG, 2023)
A total of 21 novel xanthone and acridone derivatives were synthesized using the reactions of 1,2,4-triazine derivatives with 1-hydroxy-3-methoxy-10-methylacridone, 1,3-dimethoxy-, and 1,3-dihydroxanthone, followed by optional dihydrotiazine ring aromatization. The synthesized compounds were evaluated for their anticancer activity against colorectal cancer HCT116, glioblastoma A-172, breast cancer Hs578T, and human embryonic kidney HEK-293 tumor cell lines. Five compounds (7a, 7e, 9e, 14a, and 14b) displayed good in vitro antiproliferative activities against these cancer cell lines. Compounds 7a and 7e demonstrated low toxicity for normal human embryonic kidney (HEK-293) cells, which determines the possibility of further development of these compounds as anticancer agents. Annexin V assay demonstrated that compound 7e activates apoptotic mechanisms and inhibits proliferation in glioblastoma cells.